Atributos físicos e químicos do solo e produtividade de milho em consórcio com gramíneas tropicais no sistema de integração lavoura-pecuária - Souza, Isabela Malaquias Dalto de (2018)
The crop-livestock integration system under direct seeding system increases the vegetal residues on the soil and contributes to the improvement of the physical and chemical attributes of the same, minimizing the compaction effects caused by grazing. However, forage grasses that make up the production system, along with maize, can define the success of the same, since they have different behaviors in a consortium, being able to impact in a different way the corn productivity and the physical and chemical attributes of the soil. The objective of this work was to evaluate the interrelationships between maize and forage grasses in the crop-livestock integration system during three consecutive harvests and their effects on soil physical and chemical attributes. The experiments were conducted in the municipality of Votuporanga, SP, in the 2014/15, 2015/16 and 2016/17 crops, in a randomized complete block design with four replications. The treatments were: T1 - maize in a consortium with Urochloa brizantha cv. Marandu; T2 - maize in consortium with U. ruziziensis; T3 - maize in consortium with U. hybrid DOW HD794; T4 - maize in consortium with Megathyrsus maximus cv. Aruana; T5 - single corn. The maize cultivars used were: PIONEER 30F35 (vintage 2014/15), DOW 2B710 (vintage 2015/16) and DOW 2B587 (vintage 2016/17). The productive characteristics of corn / forage grasses consortia evaluated were: maize - final plant stand, first ear insertion height, plant height, 100 grain mass, grain yield; forage grasses - production of dry biomass. The soil physical attributes evaluated were: total porosity, soil density, aggregate stability and weighted mean diameter (WMD). The chemical attributes of the soil evaluated were: pH, exchangeable bases, extractable aluminum and hydrogen, assimilable phosphorus and base saturation. The PIONEER 30F35 corn hybrid was not influenced by the consortium with forage grasses. The maize cultivar DOW 2B710 presents a smaller competitive advantage in consortium with the forage grasses U. brizantha cv. Marandu and U. hybrid under conditions of water deficit, and forage grass M. maximus cv. Aruana produced a larger amount of dry biomass in a consortium with DOW 2B587 maize and reduced grain yield of the cereal. In the first evaluation, carried out in October 2015, there was a difference between the treatments in relation to the total porosity (0-0.05 m layer) and the stability of aggregates (0-0.20 m layer) and, in relation to soil density and WMD, the treatments did not differ in any of the evaluated soil layers. In the second analysis, carried out in April 2017, the treatments differed in relation to the stability of aggregates in the three layers evaluated and in relation to the WMD (0.05-0.20 m layer). Forage grasses did not interfere in soil density, total porosity, percentage of aggregates> 2 mm and DMP. Corn treatments in consortium with forage grass provided the lowest levels of potassium and the highest values of aluminum in the soil during the experiment period.